Giant voltage-controlled modulation of spin Hall nano-oscillator damping - Himanshu Fulara (Nature Portfolio, 2020)
Spin Hall nano-oscillators can be tuned via magnetic fields and the drive current, but individual oscillator control in large arrays remains a challenge. Here, the authors provide individual control of the threshold current and the auto-oscillation frequency by voltage-controlled magnetic anisotropy.